Development Of Breast Phantoms For Ultra-wideband (Uwb) Microwave Imaging Systems - Ayob, Nur Syuhada (2023)
Ultra-wideband (UWB) microwave imaging is a promising new alternative technology for detecting breast cancer tumours in the early stages. However, the calibration kit is required in this study to obtain accurate results. Therefore, breast phantoms with properties similar to biological breast tissues (skin, fat, gland, and tumor) were created. 15 % polyvinyl alcohol (PVA), wheat flour, and deionized water were used for the fabrication of phantoms. Different wheat flour concentrations, wfc (%) (0 % to 50 %) were added to the PVA-C solution to fabricate different types of breast tissues. Lactic acid was used for preservation purposes. The dielectric properties of the fabricated phantoms were tested utilising a setup system consisting of a vector network analyzer and a dielectric coaxial probe. The reflection coefficients were measured using a fabricated insulated monopole sensor. The frequency range for all measurements was between 0.5 and 50 GHz. The dielectric properties of the fabricated phantom were found to be similar to those of real gland and tumor tissues. The wfc (%) of 79.33 %, 124.4 %, 44.13 % and 25.56 % acquired using the prediction model I have shown can be used to simulate skin, fat, gland, and tumor tissues, respectively. The results also showed agreement with the Cole-Cole model for skin, fat, gland, and tumor phantoms. This research also found that the wfc (%) in PVA-C-based breast phantoms can be determined using an insulated monopole sensor.